Seismic Imaging of Lithospheric Structure Beneath Central-East Java Region, Indonesia: Relation to Recent Earthquakes - Muttaqy, Faiz; Nugraha, Andri Dian; Mori, James; Puspito, Nanang T.; Supendi, Pepen; Rohadi, Supriyanto (Frontiers in Earth Science, 2022)
The Central and East Java region, which is part of the Sunda Arc, has an important role in producing destructive earthquakes and volcanic complexes in Indonesia as a result of the convergence between the Indo-Australian plate that subducts under the Eurasian plate. In this study, the 3-D seismic velocity structure (Vp, Vs, and Vp/Vs) of the crust and upper mantle was determined to reveal the presence of the subducted slab, volcanic sources, and seismogenic features in the Central and East Java region. We have manually re-picked P- and S-arrivals of 1,488 events from January 2009 to September 2017 recorded at 27 stations of the BMKG network. An iterative damped least-squares inversion method was applied to simultaneously calculate both hypocenter relocations and velocity structure beneath this high-risk region to a depth of 200 km. We then compare the tomographic results and seismicity to interpret structural features in the seismic zones. The subducted slab is diping toward the north, imaged by the high-velocity regions with low Vp/Vs at depths of about 50 to 100 km. Low-velocity anomalies with high Vp/Vs above the slab at a depth of ~ 100 km, imply the possible location of partial melting from slab dehydration. Fluids and melts are ascending to feed the volcanoes i.e, Merapi-Merbabu, Wilis, Pandan, Semeru, Bromo, and Ijen that also have similar low-velocity anomalies at 10-30 km depths, suggesting the presence of the sedimentary basin or magma reservoir. We also have redetermined the hypocenter location of the 2021 (Mw 6.1) Malang earthquake at 8.94oS, 112.45oE, with a depth of 59.7 km. The location error in the x, y, and z directions are 3.08, 6.39, and 11.91 km, respectively. This intraslab event with a thrusting mechanism is located in the high-velocity region and close to the intermediate-depth seismic clusters, which indicates the geometry of the oceanic slab. Related to the 1994 tsunami earthquake, we found a low-velocity anomaly at ~ 50 km depth that might be associated with the presence of subducting seamount that is more hydrated than the surrounding slab.